2022
DOI: 10.3389/fbioe.2022.852201
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Properties of Paraspinal Muscles Influence Spinal Loading—A Musculoskeletal Simulation Study

Abstract: Paraspinal muscles are vital to the functioning of the spine. Changes in muscle physiological cross-sectional area significantly affect spinal loading, but the importance of other muscle biomechanical properties remains unclear. This study explored the changes in spinal loading due to variation in five muscle biomechanical properties: passive stiffness, slack sarcomere length (SSL), in situ sarcomere length, specific tension, and pennation angle. An enhanced version of a musculoskeletal simulation model of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…To explore the influence of measured biomechanical properties on spinal loading, an enhanced validated musculoskeletal model of the lumbar spine with 210 muscles was employed [ 32 ]. Briefly, the model consisted of the sacrum and pelvis (both fixed to the ground), five mobile lumbar vertebrae connected through 6-DOF springs (representing the stiffness of each pair of adjacent vertebrae with their connecting ligaments, facet joints, and intervertebral disc along three translational and three rotational degrees of freedom); and the thoracic spine that was rigidly fixed to the L1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the influence of measured biomechanical properties on spinal loading, an enhanced validated musculoskeletal model of the lumbar spine with 210 muscles was employed [ 32 ]. Briefly, the model consisted of the sacrum and pelvis (both fixed to the ground), five mobile lumbar vertebrae connected through 6-DOF springs (representing the stiffness of each pair of adjacent vertebrae with their connecting ligaments, facet joints, and intervertebral disc along three translational and three rotational degrees of freedom); and the thoracic spine that was rigidly fixed to the L1.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the model consisted of the sacrum and pelvis (both fixed to the ground), five mobile lumbar vertebrae connected through 6-DOF springs (representing the stiffness of each pair of adjacent vertebrae with their connecting ligaments, facet joints, and intervertebral disc along three translational and three rotational degrees of freedom); and the thoracic spine that was rigidly fixed to the L1. Muscles were modeled as Hill-type musculotendon actuators, whose active and passive forces were determined using the force–length and force–velocity curves parametrized by Millard et al [ 33 ] (see [ 32 ] for further details on muscle properties and calculation of its forces).…”
Section: Methodsmentioning
confidence: 99%
“…The parameters for pennation angle, passive stiffness, sarcomere length, and specific muscle tension were constant for most of the muscle groups. However, a recent simulation study ( Malakoutian et al, 2022 ) showed the relevance of these paraspinal muscle parameters on the predicted spinal loads. To use reference material parameters, we scaled these linearly based on muscle cross-sections and body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Reported values for K vary between 10 and 100 N/cm 2 ( Daggfeldt and Thorstensson, 2003 ; Hansen et al, 2006 ). In models of the lower back, most commonly values of 46 ( Bogduk et al, 1992 ; Stokes and Gardner-Morse, 1995 ; Christophy et al, 2012 ), 60 ( Arjmand and Shirazi-Adl, 2006a ), 90 ( Arshad et al, 2016 ), or 100 N/cm 2 ( Bruno et al, 2015 ; Bayoglu et al, 2019 ; Favier et al, 2021a ; Lerchl et al, 2022 ; Malakoutian et al, 2022 ) were assumed. Thus, we tested values of 46, 73, and 100 N/cm 2 for K , expected ≤ 1.0°, and that no muscle was fully activated by the TC.…”
Section: Methodsmentioning
confidence: 99%
“…The stabilizing influence of intra-abdominal pressure (IAP) on the spine has been widely studied [124,125]. However, only a few MBS models consider its effects [38,60,63,70,77]. In consequence, spinal loads in lifting tasks or the inclination of the upper body are assumed to be overestimated in the MBS modeling of the spine.…”
Section: Intra-abdominal Pressurementioning
confidence: 99%